154k views
2 votes
Factorise y^6 - 64 as possible


2 Answers

4 votes

Answer:

(y - 2)(y + 2)(
y^(4) + 4y + 16)

Explanation:


y^(6) - 64 ← is a difference of cubes and factors in general as

a³ - b³ = (a - b)(a² + ab + b²) , then


y^(6) - 64

= (y² )³ - 4³

= (y² - 4)(
y^(4) + 4y + 16) ← note y² - 4 is a difference of squares

= (y - 2)(y + 2)(
y^(4) + 4y + 16)

User Yachi
by
5.2k points
4 votes

Answer:

Explanation:

Observe that
y^6-64=y^6-2^6.

And you factor out using this expression:


(a^6-b^6)=(a-b)(a^5+a^4b+a^3b^2+a^2b^3+ab^4+b^5)

Take a=y and b=2.

User RenegadeMind
by
5.4k points